2008
DOI: 10.1039/b818470b
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual versus algorithmic learning in high school chemistry: the case of basic quantum chemical concepts. Part 2. Students’ common errors, misconceptions and difficulties in understanding

Abstract: Part 2 of the findings are presented of a quantitative study (n = 125) on basic quantum chemical concepts taught at twelfth grade (age 17-18 years) in Greece. A paper-and-pencil test of fourteen questions was used that were of two kinds: five questions that tested recall of knowledge or application of algorithmic procedures (type-A questions); plus nine questions that required conceptual understanding and/or critical thinking (type-C questions). As a rule, performance in type-A questions was relatively high wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 28 publications
2
48
0
12
Order By: Relevance
“…We presented a protocol in this paper comprising five characteristics associated with visualization skills and metacognition; also, we portrayed high, moderate, and low levels of sophistication in participants' ability to think with mental models referring to these five characteristics. Previous studies had reported that model-based learning involves various factors including but not limited to visualization ability (Briggs and Bodner 2005;Stieff 2007;Stieff et al 2005;Wu and Shah 2004), metacognition (Gilbert 2005(Gilbert , 2008, content knowledge (Papageorgiou and Tsaparlis 2008), and understanding about the role of models and representation in scientific explanation (Bodner and Domin 2000;Treagust et al 2003Treagust et al , 2004. In this study, we addressed individual cognitive factors during mental modeling processes involving visualization and metacognition; however, this protocol is not an exhaustive list.…”
Section: Recommendations For Future Studiesmentioning
confidence: 95%
“…We presented a protocol in this paper comprising five characteristics associated with visualization skills and metacognition; also, we portrayed high, moderate, and low levels of sophistication in participants' ability to think with mental models referring to these five characteristics. Previous studies had reported that model-based learning involves various factors including but not limited to visualization ability (Briggs and Bodner 2005;Stieff 2007;Stieff et al 2005;Wu and Shah 2004), metacognition (Gilbert 2005(Gilbert , 2008, content knowledge (Papageorgiou and Tsaparlis 2008), and understanding about the role of models and representation in scientific explanation (Bodner and Domin 2000;Treagust et al 2003Treagust et al , 2004. In this study, we addressed individual cognitive factors during mental modeling processes involving visualization and metacognition; however, this protocol is not an exhaustive list.…”
Section: Recommendations For Future Studiesmentioning
confidence: 95%
“…The studies conducted by Papaphotis and Tsaparlis (2008) and Çökelez and Yalçın (2012) showed that the students' mental model of the Bohr atomic model is a more dominant model than the other atomic models. Tsaparlis and Papaphotis (2009) stated that the students prefer the Bohr atomic model because it is concrete and straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…As Papaphotis and Tsaparlis (2008) noted, the students tend to associate the concept of orbit with the concept of orbitals. The Taber (2005)'s study with Physics students revealed the students' tendency to think of quantum physics mechanically.…”
Section: Wave Orbit Modelmentioning
confidence: 99%
“…The following section describes students learning difficulties related to the understanding of atomic structure, quantization, and spin, as found in the reviewed articles [12,24,25,31,[45][46][47][48][49][50][51][52][53][54][55][56]].…”
Section: Atomsmentioning
confidence: 99%